Preparation method and application of ordered oriented magnetic fiber film

By electrostatic self-assembly of the surface charged polymer and magnetic nanoparticles, and under the control of the electric field and magnetic field, the assembly process of the magnetic fiber film is regulated, and the problems of uneven magnetic composite film materials and low mechanical properties in the prior art are solved, thereby realizing a high-performance magnetic fiber film.

CN115926221BActive Publication Date: 2025-04-08WUHAN TEXTILE UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211641025.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-20
Publication Date
2025-04-08
Estimated Expiration
2042-12-20

AI Technical Summary

Technical Problem

In the prior art, when preparing magnetic composite film materials, it is difficult to effectively control the assembly and polymer cross-linking process of magnetic nanoparticles, resulting in uneven film materials, low mechanical properties, and insufficient magnetic responsiveness.

Method used

By selecting surface-charged polymers and magnetic nanoparticles, electrostatic action is used to self-assemble to form polymer/magnetic particle nanoclusters, and under the multi-dimensional control of the electric field and magnetic field, magnetic fiber films with orderly orientation arrangements are prepared through the power-off mode control.

Benefits of technology

The uniform orientation and excellent mechanical properties of the magnetic fiber film are achieved, the magnetic responsiveness is improved, and the film generation thickness and magnetic nanoparticle content are controlled.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115926221B_ABST
    Figure CN115926221B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method and application of an orderly oriented magnetic fiber film, wherein a polymer aqueous solution is mixed with magnetic nanoparticles, and then an electrodeposition method and a magnetic field method are used to dually induce the assembly process of the film and the magnetic nanoparticles, and finally the film is soaked and solidified to obtain an orderly oriented magnetic fiber film. The surface of the magnetic nanoparticles and the polymer molecular chain of the present invention carry opposite charges respectively, and the two are self-assembled to form polymer / magnetic particle nanoclusters through electrostatic action, and under the dual action of the electric field and the magnetic field, the film and the magnetic nanoparticle assembly process are relatively regulated by the power-on-off oscillating electrical signal, so that the film intermittently grows in multiple steps, and at the same time, the multi-step enrichment assembly of the magnetic nanoparticles in the film is realized, and an orderly oriented magnetic fiber film is prepared; at the same time, the film generation thickness and the content of the magnetic nanoparticles are effectively controlled, and the overall performance of the magnetic film is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic film materials, and in particular to a preparation method and application of an orderly oriented magnetic fiber film. Background Art

[0002] Magnetic composite film materials have a wide range of uses in multi-field intelligent sensing, driving and medical fields such as magneto-optical. At present, the common method for preparing magnetic composite film materials is to add magnetic nanomaterials to the polymer precursor solution, and then cross-link the polymer under the external physical and chemical action and embed the magnetic nanomaterials in the film to form a composite magnetic film material. For example: The invention patent (application number is CN201710486163.9) discloses a method for preparing a fiber membrane loaded with oriented zinc oxide nanorods, wherein a polymer and zinc acetate are dissolved in an organic solvent, magnetic nanoparticles are added thereto, and an electrospinning solution is obtained after mixing, and an ordered polymer / zinc acetate / magnetic nanoparticle fiber is obtained by magnetic field-assisted electrospinning technology; and the fiber is subjected to low-temperature heat treatment, and finally a fiber membrane loaded with oriented zinc oxide nanorods is prepared by a hydrothermal method. However, this method and the current similar methods for preparing magnetic films generally have the following disadvantages:

[0003] (1) In order to improve the magnetic responsiveness of the composite film, it is usually achieved by increasing the concentration of magnetic nanomaterials. However, magnetic nanomaterials have poor thermal instability and are prone to aggregation. They are unevenly distributed in the polymer film. Too high a concentration will further aggravate their aggregation or cause the polymer molecules to be unable to fully cross-link into a film, making the prepared film material uneven and the mechanical properties greatly reduced.

[0004] (2) By applying an external magnetic field to induce the magnetic nanoparticles to arrange in an orderly manner along the magnetic field lines, although the performance in some aspects can be improved to a certain extent, the magnetic particles respond quickly under the action of the magnetic field, while the polymer cross-linking film formation process is relatively slow. Therefore, it is impossible to effectively control the film formation process and the assembly and arrangement of the magnetic particles to proceed in an orderly manner at the same time, which will lead to a large difference in particle distribution in the upper and lower surface areas of the film.

[0005] (3) The interface compatibility between inorganic magnetic nanomaterials with higher hardness and polymer molecules is poor, and the interaction force is weak, which also limits the improvement of the overall performance of the composite film.

[0006] Therefore, there is an urgent need in the prior art for a method for preparing a magnetic composite film that can control the assembly of magnetic nanoparticles while achieving precise and effective control of the polymer cross-linking process, and the prepared magnetic film material has a uniform structure, good mechanical properties and comprehensive properties.

[0007] In view of this, it is necessary to design an improved preparation method and application of an ordered oriented magnetic fiber film to solve the above problems. Summary of the invention

[0008] The purpose of the present invention is to provide a preparation method and application of an orderly oriented magnetic fiber film, wherein surface charged polymers and magnetic nanoparticles are selected, and the two are self-assembled through electrostatic action to form polymer / magnetic particle nanoclusters, and then under the action of multiple fields, the electric / magnetic field induced assembly process is relatively regulated through a power-on-power-off mode to prepare an orderly oriented magnetic fiber film, and the film material has better magnetic responsiveness, a uniformly oriented fibrous structure and excellent mechanical properties.

[0009] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing an orderly oriented magnetic fiber film, comprising the following steps:

[0010] S1, preparing a polymer aqueous solution, wherein the polymer is a natural high molecular polymer with a charged molecular chain;

[0011] S2, adding magnetic nanoparticles to the polymer aqueous solution of step S1, magnetically stirring for 0.5 to 4 hours, and then ultrasonically treating for 20 to 40 minutes to obtain a precursor solution containing nanoclusters; the surface of the magnetic nanoparticles has a charge opposite to the charge of the molecular chain of the polymer;

[0012] S3, using the electro-deposition method and the magnetic field method to dually induce the assembly process of the thin film and the magnetic nanoparticles; the electro-deposition method adopts an oscillating constant current mode, and uses the power-on-power-off oscillating electrical signal to regulate the assembly of the thin film and the magnetic nanoparticles; the magnetic field method induces the assembly process by means of an external magnetic field;

[0013] S4, soaking the film obtained after step S3 in a curing agent for curing, and then washing to obtain an orderly oriented magnetic fiber film.

[0014] As a further improvement of the present invention, in step S2, the added amount of the magnetic nanoparticles is expressed as a mass volume fraction of 0.7% to 1.5%; and the particle size of the magnetic nanoparticles is 5 to 80 nm.

[0015] As a further improvement of the present invention, in step S2, the size of the nanoclusters is 500-1500 nm.

[0016] As a further improvement of the present invention, the magnetic nanoparticles include magnetic ferroferric oxide nanoparticles, the surfaces of the magnetic ferroferric oxide nanoparticles carry charges opposite to the charges carried by the polymer, and the two are assembled to form nanoclusters through electrostatic interaction.

[0017] As a further improvement of the present invention, in step S3, the deposition process of the electrodeposition method is: immersing the cathode or anode electrode sheet in the precursor liquid of step S1, and adopting an oscillating constant current mode: when power is on, the applied current is i=0.08~0.09A, and the total deposition time is 300~400s; when power is off, i=0A, the time is 5~10s, and the number of cycles N is 1 to 100 times.

[0018] As a further improvement of the present invention, in the electrodeposition method, the one-step deposition conditions are: the power-on current is i=0.08~0.09A, the deposition time is 300~400s, and the number of cycles N=1; the multi-step deposition conditions are: the power-on current is i=0.08~0.09A, the deposition time is 300~400s / step, the power-off time is 5~10s, and the number of cycles N=number of steps+1.

[0019] As a further improvement of the present invention, in step S1, the polymer includes one of chitosan, alginate, silk fibroin, collagen, gelatin, and cellulose polymer, preferably chitosan.

[0020] As a further improvement of the present invention, in step S1, the polymer is chitosan, dilute hydrochloric acid is used to dissolve chitosan to obtain a chitosan solution, and deionized water is added to dilute it to obtain a chitosan aqueous solution with a mass fraction of 0.8% to 1.5%, and the pH range of the chitosan aqueous solution is 5 to 6; the concentration of the dilute hydrochloric acid is 0.1%; in step S4, the curing agent is a sodium hydroxide solution with a concentration of 0.5 to 4M.

[0021] As a further improvement of the present invention, dilute hydrochloric acid is used to dissolve chitosan. Specifically, 1 g of chitosan is dissolved in 5 mL of dilute hydrochloric acid. 95 mL of deionized water is added, and after complete dissolution, a chitosan solution with a solubility of 1% is finally obtained.

[0022] As a further improvement of the present invention, the cathode electrode sheet is a titanium electrode sheet, and the anode electrode sheet is a platinum electrode sheet.

[0023] As a further improvement of the present invention, in step S3, the control conditions of the magnetic field method are: using 3 to 5 permanent magnets with a diameter of 2.5 cm and a thickness of 0.7 cm, stacked and placed sideways to provide an external magnetic field;

[0024] The present invention also provides an application of an orderly oriented magnetic fiber film, which is applied in the field of drug controlled release; specifically, active drugs are introduced in the process of preparing nanoclusters, the nanoclusters are used as nanodrug carriers, and a light / electric / magnetic responsive drug controlled release system is constructed to give the magnetic fiber film biological activity.

[0025] The beneficial effects of the present invention are:

[0026] 1. The present invention provides a method for preparing and applying a magnetic fiber film with orderly orientation. First, a charged polymer aqueous solution is mixed with magnetic nanoparticles and stirred magnetically to obtain a precursor solution containing nanoclusters. Then, the assembly process of the film and magnetic nanoparticles is induced by dual induction of electrodeposition and magnetic field. Finally, the obtained film is soaked and solidified, and then washed to obtain an orderly oriented magnetic fiber film. The present invention selects magnetic nanoparticles and polymers with responsive charges, self-assembles to form polymer / magnetic particle nanoclusters through electrostatic action, and then relatively regulates the electric / magnetic field induced assembly process under the action of multiple fields through the power-on-power-off mode to prepare an orderly oriented magnetic fiber film. The film material has better magnetic responsiveness, uniformly oriented fibrous structure and excellent mechanical properties.

[0027] 2. The polymer and magnetic nanoparticles with charged molecular chains selected by the present invention have charges on the surface of the magnetic nanoparticles opposite to the charges carried by the polymers. The two will not only spontaneously agglomerate, but also the electrostatic effect enhances the interfacial interaction between the polymer molecular chains and the magnetic nanoparticles, effectively enhancing the interfacial bonding force between the two, so that they self-assemble to form polymer / magnetic particle nanoclusters. When the electric field and the magnetic field are controlled in multiple dimensions, because the magnetic nanoparticles and the polymer molecular chains exist in the structure of nanoclusters, the ordered arrangement of nanoclusters can be formed while the magnetic field induces the orderly arrangement of the magnetic nanoparticles, so that the polymer molecular chains are oriented to a certain extent, and the polymer molecules are deprotonated under the induction of the electric field to self-assemble cross-linked film in situ on the electrode surface, thereby improving the mechanical properties of the film and obtaining an ordered fibrous structure magnetic composite film with excellent comprehensive performance and relatively uniform distribution of magnetic nanoparticles.

[0028] 3. The present invention realizes the in-situ controllable self-assembly of composite nanoclusters by using oscillating electrical signals through the power-on-power-off mode, and relatively regulates the assembly process of the film and magnetic nanoparticles, so that the film grows intermittently in multiple steps, and at the same time realizes the multi-step enrichment assembly of magnetic nanoparticles in the film, so that the magnetic particles are evenly distributed in the upper and lower surface areas of the film, thereby improving the magnetic response performance of the film; and through this mode, effective control of the film generation thickness and the content of magnetic nanoparticles is achieved, further improving the overall performance of the magnetic composite film.

[0029] 4. In the process of preparing polymer / magnetic particle nanoclusters, the present invention controls the particle size of magnetic nanoparticles and the amount of magnetic nanoparticles added in the polymer aqueous solution, so that the magnetic nanoparticles can exert a thermal aggregation effect, which is beneficial to the assembly of nanoclusters. At the same time, magnetic stirring is used to make the magnetic nanoparticles and polymer molecules fully contact, which provides a basis for them to form nanoclusters through electrostatic action. By controlling the time of ultrasonic treatment, the size of the formed nanocluster structure is suitable and the structure is uniform, which is beneficial to the orderly arrangement of the nanocluster structure during subsequent multi-field induction. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the self-assembly process of chitosan / Fe3O4 nanoclusters in Example 1 of the present invention.

[0031] Figure 2 This is the electron microscope and elemental analysis diagram of chitosan / Fe3O4 magnetic particle nanoclusters prepared in Example 1 of the present invention.

[0032] Figure 3 Magnified SEM image and elemental analysis image of the magnetic film in Example 1 of the present invention.

[0033] Figure 4 This is a graph showing the Zeta potential test results of the nanoclusters and single-component magnetic ferroferric oxide nanoparticles and chitosan prepared in Example 1 and Comparative Examples 1-2 of the present invention.

[0034] Figure 5 The dynamic light scattering DLS test results of Example 1, Comparative Examples 1 to 2 and magnetic ferroferric oxide nanoparticles of the present invention are shown.

[0035] Figure 6 Schematic diagram and SEM image of the preparation of magnetic fiber films according to Examples 1 to 2 of the present invention and Comparative Example 3.

[0036] Figure 7 Graph showing the test results of hysteresis curves of the magnetic films prepared in Examples 1-2 of the present invention and Comparative Examples 3-4.

[0037] Figure 8 The mechanical property test curves of the films prepared in Examples 1-2 and Comparative Examples 3-4 of the present invention are shown.

[0038] Fig. 9 The electron microscope images of the thin film cross sections of Example 2 and Comparative Example 4 of the present invention are shown.

[0039] Fig.10 The following are appearance diagrams of magnetic fiber films of different shapes prepared by the preparation method of Example 1 of the present invention. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0041] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.

[0042] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0043] A method for preparing an orderly oriented magnetic fiber film comprises the following steps:

[0044] S1, preparing a polymer aqueous solution, wherein the polymer is a natural high molecular polymer with a charged molecular chain;

[0045] S2, adding magnetic nanoparticles to the polymer aqueous solution of step S1, magnetically stirring for 0.5 to 4 hours, and then ultrasonically treating for 20 to 40 minutes to obtain a precursor solution containing nanoclusters; wherein the surface of the magnetic nanoparticles carries a charge opposite to the charge of the polymer molecular chain; the amount of the magnetic nanoparticles added is expressed as a mass volume fraction, which is 0.7% to 1.5%; the particle size of the magnetic nanoparticles is 5 to 80 nm; the size of the nanoclusters is 500 to 1500 nm;

[0046] In the process of preparing polymer / magnetic particle nanoclusters, the particle size of magnetic nanoparticles and the amount of magnetic nanoparticles added in the polymer aqueous solution are controlled so that the magnetic nanoparticles can better exert the thermal aggregation effect, which is beneficial to the assembly of nanoclusters; at the same time, magnetic stirring is used to make the magnetic nanoparticles and polymer molecules fully contact, which provides a basis for them to form nanoclusters through electrostatic action. By controlling the time of ultrasonic treatment, the size of the formed nanocluster structure is suitable and the structure is uniform, which is beneficial to the orderly arrangement of the nanocluster structure during subsequent multi-field induction;

[0047] S3, using the electro-deposition method and the magnetic field method to dually induce the assembly process of the thin film and the magnetic nanoparticles; the electro-deposition method uses an oscillating constant current mode, and uses the power-on-power-off oscillating electrical signal to regulate the assembly of the thin film and the magnetic nanoparticles; the magnetic field method is to induce the assembly process by means of an external magnetic field;

[0048] S4, soaking the film obtained after step S3 in a curing agent for curing, and obtaining an orderly oriented magnetic fiber film after washing.

[0049] In this preparation method, the selected polymers and magnetic nanoparticles with charge response will not only spontaneously agglomerate, but also the electrostatic effect will enhance the interface interaction between the polymer molecular chain and the magnetic nanoparticles, effectively enhancing the interface binding force between the two, so that they self-assemble to form polymer / magnetic particle nanoclusters. When the electric field and magnetic field are controlled in multiple dimensions, because the magnetic nanoparticles and polymer molecular chains exist in the structure of nanoclusters, the magnetic field induces the orderly arrangement of magnetic nanoparticles, and at the same time, the orderly arrangement of nanoclusters can be formed, so that the polymer molecular chains are oriented to a certain extent, and the polymer molecules are deprotonated under the induction of the electric field to self-assemble and cross-link on the electrode surface to form a film in situ, which improves the mechanical properties of the film, and obtains a magnetic composite film with an ordered fibrous structure with excellent comprehensive performance and relatively uniform distribution of magnetic nanoparticles; the film material has better magnetic responsiveness, uniformly oriented fibrous structure and excellent mechanical properties.

[0050] Specifically, in step S3, the deposition process of the electrodeposition method is: immerse the cathode or anode electrode sheet in the precursor solution of step S1, and adopt an oscillating constant current mode: when the power is on, the applied current is i=0.08~0.09A, the total deposition time is 300~400s, when the power is off, i=0A, the time is 5~10s, and the number of cycles N is 1~100 times. One-step deposition conditions: the power-on current is i=0.08~0.09A, the deposition time is 300~400s, and the number of cycles N=1; multi-step deposition conditions: the power-on current is i=0.08~0.09A, the deposition time is 300~400s / step, the power-off time is 5~10s, and the number of cycles N=number of steps+1.

[0051] Through the above-mentioned power-on-off mode, the in-situ controllable self-assembly of composite nanoclusters is achieved by utilizing oscillating electrical signals, and the assembly process of the film and magnetic nanoparticles is relatively regulated, so that the film grows intermittently in multiple steps, and at the same time, the multi-step enrichment assembly of magnetic nanoparticles in the film is achieved, so that the magnetic particles are evenly distributed in the upper and lower surface areas of the film, thereby improving the magnetic response performance of the film; and through this mode, effective control of the film generation thickness and the content of magnetic nanoparticles is achieved, further improving the overall performance of the magnetic composite film.

[0052] Specifically, the polymer includes one of chitosan, alginate, silk fibroin, collagen, gelatin, and cellulose polymer, preferably chitosan. The magnetic nanoparticles include magnetic ferroferric oxide nanoparticles, the surface of which carries a charge opposite to the molecular chain charge of the polymer, and the two assemble to form nanoclusters through electrostatic interaction.

[0053] In some specific embodiments, when the polymer is chitosan, dilute hydrochloric acid is used to dissolve chitosan to obtain a chitosan solution, and deionized water is added to dilute it to obtain a chitosan aqueous solution with a mass fraction of 0.8% to 1.5%, and the pH range of the chitosan aqueous solution is 5 to 6. When using dilute hydrochloric acid to dissolve chitosan, specifically, 1g of chitosan is dissolved for every 5mL of dilute hydrochloric acid, and 95mL of deionized water is added to obtain the solubility of the chitosan solution after complete dissolution; the concentration of dilute hydrochloric acid is 0.1%. Because the polymer uses positively charged chitosan, in step S3, a cathode electrode sheet is selected to be immersed in the precursor liquid for electrodeposition film formation, and in step S4, a curing agent is selected from a sodium hydroxide solution with a concentration of 0.5 to 4M.

[0054] In other embodiments, the preparation method of the polymer aqueous solution, whether the electrodeposition method is cathode film formation or anode film formation, and the type of curing agent are all adjusted according to the type of natural high molecular polymer selected.

[0055] In some specific embodiments, the cathode electrode sheet is a titanium electrode sheet with a size of (3.5*2.5*0.05 cm) and a depth of 3 cm immersed in the precursor liquid; the anode is a platinum electrode sheet with a length of 3.5 cm.

[0056] In some specific embodiments, in step S3, the control conditions of the magnetic field method are: using 3 to 5 permanent magnets with a diameter of 2.5 cm and a thickness of 0.7 cm, stacked and placed sideways to provide an external magnetic field. It should be noted that the effect of the external magnetic field of the present invention is different from the traditional preparation of magnetic films by magnetic fields. In the present invention, magnetic composite nanoclusters are formed in advance, and the interface binding force between the polymer and the magnetic nanoparticles is strong. Under the action of the magnetic field, the orderly arrangement of the magnetic nanoparticles is induced, which drives the relative orientation of the polymer macromolecules, thereby causing the entire magnetic composite nanocluster to be orderly oriented.

[0057] The present invention also provides an application of an orderly oriented magnetic fiber film, which can be applied to the field of drug controlled release; specifically, active drugs are introduced into the process of preparing nanoclusters, and the nanoclusters are used as nanodrug carriers to construct a light / electricity / magnetic response drug controlled release system, thereby giving the magnetic fiber film biological activity.

[0058] In some other fields, the magnetic film can be further functionalized, for example, by adding conductive nanofillers to give it conductive properties and use it as an electrolyte film material.

[0059] Example 1

[0060] This embodiment provides a method for preparing an orderly oriented magnetic fiber film, comprising the following steps:

[0061] S1, dissolving chitosan powder with dilute hydrochloric acid to obtain a chitosan solution, and diluting with water to obtain a chitosan aqueous solution with a mass fraction of 1% (w / v) (pH of 5.5);

[0062] S2, adding 0.5 g of magnetic ferroferric oxide nanoparticles (particle size of 50 nm) with negative surface charge (i.e., carboxyl modified) to 50 mL of chitosan aqueous solution of step S1, stirring magnetically for 2 h, and then ultrasonically treating for 30 min to obtain a precursor solution containing nanoclusters (size of 600 nm);

[0063] S3, the assembly process of the film and magnetic Fe3O4 nanoparticles by dual induction of electrodeposition and magnetic field;

[0064] Electrodeposition method: a titanium electrode sheet (cathode, size 3.5*2.5*0.05cm) is immersed in the precursor solution of step S1 to a depth of 3cm, and the anode is a platinum wire with a length of 3.5cm; an oscillating constant current mode is adopted, the deposition step number is one step, the cathode current applied when power is on is i=0.084A, the deposition time is 360s, when power is off, i=0A, the time is 5s, and the number of cycles N=1 times;

[0065] Magnetic field method: Five permanent magnets with a diameter of 2.5 cm and a thickness of 0.7 cm are stacked and placed sideways to provide an external magnetic field;

[0066] S4, soaking the film obtained after step S3 in a sodium hydroxide solution with a concentration of 1 mol / L for solidification for 5 minutes, and then washing to obtain an orderly oriented magnetic fiber film.

[0067] See also Figure 1 FIG. 1 is a schematic diagram of the self-assembly process of the chitosan / Fe3O4 nanoclusters of Example 1. As can be seen from the figure, the chitosan with positive charge on the molecular chain and the magnetic Fe3O4 nanoparticles with negative charge on the surface will spontaneously agglomerate, and at the same time, the interface interaction between the polymer and the magnetic nanoparticles is enhanced by electrostatic action, which effectively enhances the interfacial bonding force between the two, and self-assembles to form chitosan / Fe3O4 magnetic particle nanoclusters.

[0068] See also Figure 2 The figure shows the electron microscope and elemental analysis of chitosan / Fe3O4 magnetic particle nanoclusters prepared in Example 1. As can be seen from the figure, the nanoclusters were successfully prepared in this example, and the nanoclusters mainly include C, N, O and Fe elements, indicating that they are mainly composed of chitosan and Fe3O4 magnetic particles.

[0069] See also Figure 3, which are the enlarged SEM images and elemental analysis images of the magnetic film in Example 1. It can be seen from the figure that nanoclusters are formed by chitosan and Fe3O4 magnetic particles, and the nanoclusters are assembled into magnetic fibers under the action of magnetic and electric fields.

[0070] Comparative Examples 1-2

[0071] Comparative Examples 1 to 2 provide a method for preparing an orderly oriented magnetic fiber film. Compared with Example 1, the difference is that in step S2, the added amounts of magnetic ferrosoferric oxide nanoparticles are 0.125 g and 1 g, respectively. The rest is roughly the same as Example 1 and will not be repeated here.

[0072] See also Figure 4 The figure shows the Zeta potential test results of the nanoclusters prepared in Example 1 and Comparative Examples 1-2 and the single-component magnetic ferroferric oxide nanoparticles and chitosan; the amount of magnetic nanoparticles added is expressed as mass volume fraction (w / v), which is 1% in Example 1, 0.25% in Comparative Example 2, and 2% in Comparative Example 3. Figure 4 It can be seen that after adding magnetic ferroferric oxide nanoparticles, they will form composite nanoclusters with chitosan molecular chains through electrostatic action, and with different addition amounts, nanoclusters of different sizes will be formed, and they will show different Zeta potential values. The final nanoclusters also show positive potential. This result also shows that the introduction of magnetic ferroferric oxide has no significant effect on the overall Zeta potential of the chitosan solution, and can still ensure the smooth implementation of the electrophoretic deposition process.

[0073] See also Figure 5 As shown, the dynamic light scattering DLS test results of Example 1, Comparative Examples 1-2 and magnetic ferroferric oxide nanoparticles; wherein the amount of magnetic nanoparticles added is expressed as mass volume fraction (w / v), which is 1% for Example 1, 0.25% for Comparative Example 2, and 2% for Comparative Example 3. It can be seen from the figure that when the amount of magnetic Fe3O4 nanoparticles added is 1%, the size distribution of the prepared nanoclusters is relatively uniform, concentrated between 500 and 1500nm; while the size distribution of the nanoclusters prepared in Comparative Examples 2 and 3 is uneven, which is not conducive to the subsequent induction of the magnetic field on the nanoclusters, and the uniformity of the formed magnetic film is poor.

[0074] Example 2

[0075] This embodiment provides a method for preparing an orderly oriented magnetic fiber film. Compared with Example 1, the difference is that in the electroplating method in step S3, a four-step deposition is adopted: the power-on current is i=0.084A, the deposition time is 90s, when the power is off, i=0A, the time is 5s, and the number of cycles N=5; the rest is roughly the same as Example 1 and will not be repeated here.

[0076] Comparative Example 3

[0077] Comparative Example 3 provides a method for preparing a magnetic thin film. Compared with Example 1, the difference is that in step S3, only the electrodeposition method is used, and the magnetic field method is not used; the rest is roughly the same as Example 1 and will not be repeated here.

[0078] See also Figure 6 As shown, Figure 6 The schematic diagram and SEM image of the preparation of magnetic fiber film for Examples 1-2 and Comparative Example 3. It can be seen from the figure that in Comparative Example 3, the magnetic film prepared by only electrodeposition method has disordered magnetic Fe3O4 nanoparticles inside, with a content of 21%, and the obtained film does not have a special fibrous structure. In Example 1, under the dual induction of electric field and magnetic field, an orderly oriented magnetic fiber film is prepared, the surface of the film is a fibrous structure, and the width of the magnetic fiber formed by the nanoclusters is 28μm, and the content of magnetic Fe3O4 nanoparticles in the film is 56%. In Example 2, through the power-on-off mode, the oscillating electrical signal is used to realize the in-situ controllable self-assembly of the composite nanoclusters, so that the film grows intermittently in multiple steps, and at the same time, the multi-step enrichment assembly of magnetic nanoparticles in the film is realized, and the width of the magnetic fiber is 42μm, the surface of the film is a fibrous structure, and the content of magnetic Fe3O4 nanoparticles in the film is 73%, which further improves the overall performance of the magnetic composite film.

[0079] Comparative Example 4

[0080] Comparative Example 4 provides a method for preparing a magnetic thin film. Compared with Example 2, the difference is that in step S3, only the electrodeposition method is used, and the magnetic field method is not used; the rest is roughly the same as Example 1 and will not be repeated here.

[0081] See also Figure 7 As shown, the hysteresis curve test results of the magnetic films prepared in Examples 1 to 2 and Comparative Examples 3 to 4 are shown, wherein Example 1 is a Monolayer magnetic curve, Example 2 is a Multilayer magnetic curve, Comparative Example 3 is a Monolayer No magnetism curve, and Comparative Example 4 is a Multilayer No magnetism curve. Figure 7 The left figure shows that the hysteresis curves of the prepared samples are relatively narrow, showing that they are soft magnetic materials. 4G, the magnetic induction intensity of the four samples all reached the saturation value, and under the action of the magnetic field, the saturation magnetic induction value of the thin film sample (Multilayer magnetic) prepared by multi-step cyclic deposition can reach nearly 38emu / g, which is significantly higher than other samples. From the right figure (partial enlarged figure), it can be seen that the remanent magnetic intensity of each sample (when the external magnetic field is 0) is not 0, indicating that they all contain magnetic ferroferric oxide nanoparticles, among which the remanent magnetic intensity of the thin film prepared under the condition of magnetic field is greater than that of the sample without magnetic field; and the remanent magnetic intensity of the thin film prepared by multi-step electrodeposition (Multilayer magnetic) is significantly higher than that of the sample prepared by one-step method (Monolayer magnetic); mainly because under the premise of the same total power-on time, the additional power-off time and number of times in the multi-step cycle process can effectively increase the total time of magnetic field action, thereby increasing the final film magnetic particle content; on the contrary, when there is no magnetic field, the remanent magnetic intensity of the samples prepared by one or more step cyclic deposition has no obvious difference and is relatively low, indicating that the content of magnetic particles is small and the magnetic properties of the film are poor.

[0082] See also Figure 8 The figure shows the mechanical properties test curves of the films prepared in Examples 1-2 and Comparative Examples 3-4, wherein the films of Example 1 and Example 2 were tested for longitudinal stretching and transverse stretching, respectively. It can be seen from the figure that the mechanical properties of the film materials of Examples 1-2 are better than those of the films prepared in Comparative Examples 3-4 without applying an external magnetic field; and the film of Example 2 has the best mechanical properties.

[0083] See also Fig. 9 The figure shows the cross-sectional electron microscope images of the films of Example 2 and Comparative Example 4. It can be seen from the figure that the film in Comparative Example 4 forms a layered structure under electric field deposition; however, in Example 2, the magnetic nanoparticles are orderly arranged by an external magnetic field, and the nanoclusters formed by the magnetic nanoparticles and the polymer form magnetic fibers between the distributed and deposited films through the regulation of the oscillation signal, so that the film has no layered structure, and a magnetic fiber film with orderly and uniform arrangement of magnetic fibers is obtained.

[0084] See also Fig.10 As shown, Fig.10 The following are appearance pictures of magnetic fiber films of different shapes prepared by the preparation method of Example 1. It can be seen from the figure that magnetic fiber films of different shapes can be prepared by changing the shape of the cathode; in addition, it can be seen that the film can be peeled off from the surface of the metal titanium electrode to form a self-supporting composite film with good performance.

[0085] Comparative Example 5

[0086] Comparative Example 5 provides a method for preparing a magnetic thin film. Compared with Example 1, the difference is that in step S3, coating is used to form a film, and 1M sodium hydroxide is used for cross-linking for 10 minutes, and an external magnetic field is applied; the rest is roughly the same as Example 1 and will not be repeated here.

[0087] The magnetic films prepared in Examples 1 to 2 and Comparative Examples 1 to 5 were tested for magnetization intensity and mechanical properties, and the results are shown in the following table.

[0088] Table 1 Performance indexes of magnetic films of Examples 1 to 2 and Comparative Examples 1 to 5

[0089] Saturation magnetization (emu / g) Tensile strength(MPa) Example 1 36.3 0.183 Example 2 38.9 0.325 Comparative Example 1 35.5 0.165 Comparative Example 2 37.2 0.213 Comparative Example 3 35.2 0.138 Comparative Example 4 35.4 0.125 Comparative Example 5 34.8 0.258

[0090] As shown in Table 1, under the simultaneous application of electric and magnetic fields, the magnetization and mechanical properties of the composite film are improved to a certain extent with the increase in the amount of ferroferric oxide nanoparticles input. This is because the magnetic particles migrate significantly along the magnetic field lines under the action of the external magnetic field and aggregate on the electrode surface. In addition, the multi-step cyclic deposition process can significantly improve its magnetization because the intermittent power-off process can provide additional time for the magnetic field to act, inducing more magnetic particles to aggregate on the film surface. However, when no magnetic field is applied, the migration of magnetic particles in the solution is weak, so the magnetization and tensile strength of the generated film are small, and the increase in the amount of magnetic particles input does not significantly improve the performance of the film. In summary, the dual effects of oscillating electric field / external magnetic field can effectively increase the content of magnetic particles in the film, thereby significantly improving the magnetization and mechanical properties of the film.

[0091] It can be seen from Comparative Example 5 that the magnetic thin film material prepared by traditional coating film formation under the condition of an external magnetic field has poor magnetization intensity, and the tensile strength of the wet film is also worse than that of the ordered oriented magnetic fiber film prepared by multi-step cyclic deposition in the present invention.

[0092] In summary, the present invention provides a method for preparing and applying a magnetic fiber film with orderly orientation arrangement, firstly, a polymer aqueous solution is mixed with magnetic nanoparticles, and magnetic stirring is performed to obtain a precursor liquid containing nanoclusters; then, an electrodeposition method and a magnetic field method are used to double-induce the assembly process of the film and the magnetic nanoparticles; finally, the film obtained after the double induction is soaked and solidified, and the magnetic fiber film with orderly orientation arrangement is obtained after washing. The surface of the magnetic nanoparticles selected by the present invention and the polymer molecular chain carry opposite charges respectively, and the two are self-assembled to form polymer / magnetic particle nanoclusters through electrostatic action, and continue to realize the in-situ controllable self-assembly of the composite nanoclusters through the dual action of the electric field and the magnetic field, through the power-on-off oscillating electrical signal, the film and the magnetic nanoparticle assembly process are relatively regulated, so that the film grows intermittently in multiple steps, and the multi-step enrichment assembly of the magnetic nanoparticles in the film is realized, and the magnetic fiber film with orderly orientation arrangement is prepared, and the film performance is improved; at the same time, the effective control of the film generation thickness and the content of the magnetic nanoparticles is realized, and the overall performance of the magnetic composite film is further improved; the film material has better magnetic responsiveness, uniformly oriented fibrous structure and excellent mechanical properties.

[0093] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an orderly oriented magnetic fiber film, characterized in that: The following steps are involved: S1, preparing a polymer aqueous solution, wherein the polymer is a natural high molecular polymer with a charged molecular chain; S2, adding magnetic nanoparticles to the polymer aqueous solution of step S1, magnetically stirring for 0.5 to 4 hours, and then ultrasonically treating for 20 to 40 minutes to obtain a precursor solution containing nanoclusters; the surface of the magnetic nanoparticles carries a charge opposite to the charge of the molecular chain of the polymer; The amount of the magnetic nanoparticles added is expressed as a mass volume percentage of the magnetic nanoparticles and the polymer aqueous solution, which is 0.7% to 1.5%; the magnetic nanoparticles include magnetic ferroferric oxide nanoparticles, which have a charge opposite to that of the polymer, and the two are assembled to form nanoclusters through electrostatic interaction; The polymer is chitosan, chitosan is dissolved in dilute hydrochloric acid to obtain a chitosan solution, and deionized water is added to dilute the chitosan solution to obtain a chitosan aqueous solution with a mass fraction of 0.8% to 1.5%, and the pH range of the chitosan aqueous solution is 5 to 6; S3, using electroplating and magnetic field method to dually induce the assembly process of thin film and magnetic nanoparticles; the electroplating method adopts an oscillating constant current mode, and uses an oscillating electrical signal of power on-off to regulate the assembly of thin film and magnetic nanoparticles; the magnetic field method is to induce the assembly process by means of an external magnetic field; the deposition process of the electroplating method is: immersing the cathode or anode electrode sheet in the precursor liquid of step S2, using an oscillating constant current mode: when power is on, the applied current is i=0.08~0.09A, the total deposition time is 300~400s, when power is off, i=0A, the time is 5~10s, and the number of cycles N is 1~100 times; the control conditions of the magnetic field method are: using a permanent magnet with a diameter of 2.5cm and a thickness of 0.7cm, 3~5 are stacked and placed sideways to provide an external magnetic field; S4, soaking the film obtained after step S3 in a curing agent for curing, and then washing to obtain an orderly oriented magnetic fiber film.

2. The method for preparing an orderly oriented magnetic fiber film according to claim 1, characterized in that: In step S2, the particle size of the magnetic nanoparticles is 5-80 nm.

3. The method for preparing an orderly oriented magnetic fiber film according to claim 1, characterized in that: In step S2, the size of the nanoclusters is 500-1500 nm.

4. The method for preparing an orderly oriented magnetic fiber film according to claim 1, characterized in that: In the electrodeposition method, the one-step deposition conditions are: the current i=0.08~0.09 A, the deposition time is 300~400 s, and the number of cycles N=1; the multi-step deposition conditions are: the current i=0.08~0.09 A, the deposition time is 300~400 s / step, the power-off time is 5~10 s, and the number of cycles N=number of steps+1.

5. The method for preparing an orderly oriented magnetic fiber film according to claim 1, characterized in that: In step S1, the concentration of the dilute hydrochloric acid is 0.1%; in step S4, the curing agent is a sodium hydroxide solution with a concentration of 0.5-4 M.

6. Use of an orderly oriented magnetic fiber film prepared by the preparation method according to any one of claims 1 to 5 in preparing a drug controlled release system, characterized in that: Active drugs are introduced during the preparation of nanoclusters in the preparation method. The nanoclusters are used as nano drug carriers, and a light / electricity / magnetic response drug controlled release system is constructed to give the magnetic fiber film biological activity.

Citation Information

Patent Citations

  • Preparing method for oriented-zinc-oxide-nanometer-bar-loaded fiber membrane

    CN107237043A

  • Method and device for preparing high-strength and high-conductivity copper-carbon nano-tube composite material under magnetic field

    CN105696059A

  • Aeolotropic magnetic high polymer composite film material and preparation method thereof

    CN108102121A